2005
DOI: 10.1590/s0100-879x2005000700009
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-dependent hemolytic activity of Passiflora quadrangularis leaves

Abstract: Plants used in traditional medicine are rich sources of hemolysins and cytolysins, which are potential bactericidal and anticancer drugs. The present study demonstrates for the first time the presence of a hemolysin in the leaves of Passiflora quadrangularis L. This hemolysin is heat stable, resistant to trypsin treatment, has the capacity to froth, and acts very rapidly. The hemolysin activity is dose-dependent, with a slope greater than 1 in a double-logarithmic plot. Polyethylene glycols of high molecular w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Accordingly, thermal treatments above 100 °C such as cooking and roasting, are sufficient to eliminate this anti-nutritional component, present in the pequi skin flours. On the other hand, hemolysins are important compounds from the biotechnological point of view, given the potential bactericidal and anticancer activities (YULDASHEVA et al, 2005).…”
Section: Antinutritional Factorsmentioning
confidence: 99%
“…Accordingly, thermal treatments above 100 °C such as cooking and roasting, are sufficient to eliminate this anti-nutritional component, present in the pequi skin flours. On the other hand, hemolysins are important compounds from the biotechnological point of view, given the potential bactericidal and anticancer activities (YULDASHEVA et al, 2005).…”
Section: Antinutritional Factorsmentioning
confidence: 99%
“…30 Whole blood samples were first mixed (1∶1; v∕v) with anticoagulant acid citrate dextrose (ACD) solution. In the next step, cNDs of sizes 5 and 100 nm were added to the citrated blood samples (100 μl) in concentrations of 5 μg∕ml and 50 μg∕ml and were incubated for 3 h. Solutions were centrifuged at 160 g (1000 rpm) and 25°C, for 10 min.…”
Section: Hemolysis Analysismentioning
confidence: 99%
“…There are many bioactive phytochemicals in the leaves of these vegetables and at present, it is not certain, which of them is/ are responsible for the observed effects. Reports have shown that flavonoids, tannins, and saponins may play some roles in hypolipidaemic effect (Ezekwe and Obidoa, 2001;Nwanjo, 2005;Yuldasheva et al, 2005). In this study the hypolipidaemic effects of the two diet preparations were compared and it was observed that Telfairia occidentalis elicited a greater effect than Gongronema latifolium.…”
Section: Discussionmentioning
confidence: 84%